2021
DOI: 10.3390/genes12050784
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Potassium Channel Genes in Rice: Expression of the OsAKT and OsKAT Genes under Salt Stress

Abstract: Potassium (K+), as a vital element, is involved in regulating important cellular processes such as enzyme activity, cell turgor, and nutrient movement in plant cells, which affects plant growth and production. Potassium channels are involved in the transport and release of potassium in plant cells. In the current study, three OsKAT genes and two OsAKT genes, along with 11 nonredundant putative potassium channel genes in the rice genome, were characterized based on their physiochemical properties, protein struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 82 publications
2
39
0
Order By: Relevance
“…Moreover, sub-groups of MGTs in the three studied plants showed diversity in the predicted pocket sites in the 3D structure. Overall, our findings suggest that PHE, GLU, LEU, GLY, and ILE, as the key binding sites, are associated with the function and interaction of MGTs in response to environmental stimuli and changes in ion/Mg concentration [54,75,76].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Moreover, sub-groups of MGTs in the three studied plants showed diversity in the predicted pocket sites in the 3D structure. Overall, our findings suggest that PHE, GLU, LEU, GLY, and ILE, as the key binding sites, are associated with the function and interaction of MGTs in response to environmental stimuli and changes in ion/Mg concentration [54,75,76].…”
Section: Discussionmentioning
confidence: 64%
“…Notably, a gene cluster of three MRS2/TcMGT genes, namely TcMGT013, TcMGT14, and TcMGT15, was observed in chromosome 6, providing an avenue for further molecular investigations in cacao. In addition, the K a /K s ratios in most duplicated genes were less than one, suggesting that MGTs have evolved slowly under a purifying selection [54,71]. The comparisons between structures of MGT proteins revealed that NIPA proteins include the conserved structures with more transmembrane regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparing with Arabidopsis , much less is known about the mechanism underlying K + absorption and translocation in rice plants. Although OsAKT1 and OsHAK5, like AtAKT1 and AtHAK5, mediate K + uptake in rice roots ( Li et al, 2014 ; Yang et al, 2014 ), K + channels such as OsKATs and OsAKTs may be involved in K + accumulation in the cytoplasm in response to salt stress ( Musavizadeh et al, 2021 ). Thus, more transporters related to K + absorption and translocation need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The change in membrane conformation that results in a decrease in membrane fluidity is one of the first structural changes related to low-temperature stress [5]. Furthermore, the alteration of membrane conformation can cause oxidative stress by rapidly inducing reactive oxygen species (ROS), and then, the concentration of cryoprotective compounds increases in the cytoplasmic matrix [2,6,7]. However, plants use various mechanisms, including morphological and structural modifications, as well as biochemical mechanisms to modulate cellular homoeostasis to reduce low, nonfreezing temperature-induced damage [2,8,9].…”
Section: Introductionmentioning
confidence: 99%